Challenges and strategies in English-medium learning among Chinese international students in a Malaysian university - Zhangli, Wu; Xuewen, Wang; Ismail, Lilliati; Khaiessa Ahmad, Norhakimah; Mahfoodh, Omer Hassan Ali (SAGE Publications, 2025)
This study examined the challenges of English learning encountered by Chinese international students in a Malaysian university, as well as the contributing factors and strategies students employ to cope with these challenges. A total of 60 Chinese international students (51.7% male and 48.3% female) participated in this study, with an average stay of 8.5 months in Malaysia. The study adopted a sequential mixed-methods approach, utilizing both quantitative and qualitative methods of data collection. Quantitative data were gathered through a questionnaire, while qualitative data were collected via interviews. Descriptive analysis was used to identify students’ challenges, while T-tests and ANOVA were conducted to examine statistical differences based on gender and academic qualifications. The contributing factors and students’ coping strategies were identified through thematic analysis of the interviews. The results indicated that participants acknowledged challenges in English language learning, particularly in speaking and listening. Additionally, significant statistical differences were found across different academic qualification levels. These findings provide deeper insights into the English learning problems faced by Chinese international students and contribute to a greater understanding of how academic qualifications impact foreign language education.